Scenario development and foresight analysis: Exploring options to inform choices - Wiebe, Keith D.; Zurek, Monika; Lord, Steven; Brzezina, Natalia; Gabrielyan, Gnel; Libertini, Jessica; Loch, Adam; Thapa-Parajuli, Resham; Vervoort, Joost; Westhoek, Henk (Annual Reviews, 2018)
In an increasingly globalized and interconnected world, where social and environmental change occur ever more rapidly, careful futures-oriented thinking becomes crucial for effective decision making. Foresight activities, including scenario development, quantitative modeling, and scenario-guided design of policies and programs, play a key role in exploring options to address socioeconomic and environmental challenges across many sectors and decision-making levels. We take stock of recent methodological developments in scenario and foresight exercises, seek to provide greater clarity on the many diverse approaches employed, and examine their use by decision makers in different fields and at different geographic, administrative, and temporal scales. Experience shows the importance of clearly formulated questions, structured dialog, carefully designed scenarios, sophisticated biophysical and socioeconomic analysis, and iteration as needed to more effectively link the growing scenarios and foresight community with today's decision makers and to better address the social, economic, and environmental challenges of tomorrow.